Association of ground hardness with injuries in rugby union. Issue 9 (15th May 2007) - Takemura, Masahiro; Schneiders, Anthony G; Bell, Melanie L; Milburn, Peter D
Abstract : Background: Ground hardness is considered one of the possible risk factors associated with rugby injuries. Objectives: To examine the contribution of ground hardness, rainfall and evapotranspiration to the incidence of injury, and to investigate seasonal injury bias throughout one full season of rugby union. Methods: A prospective epidemiological study of rugby injuries was performed on 271 players from rugby union teams involved in the premier grade rugby competition in Dunedin, New Zealand. Ground hardness was measured before each match over 20 rounds with an industrial penetrometer, and local weather information was collected through the National Institute of Weather and Atmospheric Research and the Otago Regional Council. Poisson mixed models were used to describe injury incidence as a function of ground hardness throughout the season. Results: The overall injury incidence during the season was 52 injuries per 1000 match player-hours (95% CI 42 to 65). Although injury incidence decreased gradually by round with a rate ratio of 0.98 (95% CI 0.96 to 0.99) (p = 0.036), and the hardness of match grounds decreased significantly over the season (0.16 MPa/round, 95% CI 0.12 to 0.21, p<0.001), a non-significant association was demonstrated between injury incidence and ground hardness. Injury incidence was not associated with a combination of ground hardness, rainfall and evapotranspiration on the day of the match or cumulative rainfall and evapotranspiration before each match. Conclusions: Seasonal change in ground hardness and an early-season bias of injuries was demonstrated. Although the contribution of ground hardness to injury incidence was not statistically significant, match round and injury incidence were highly correlated, confirming a seasonal bias, which may confound the relationship of injury to ground condition.